2021
DOI: 10.1038/s41467-021-21753-9
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of the Survivin–CRM1 interaction by peptide-modified molecular tweezers

Abstract: Survivin’s dual function as apoptosis inhibitor and regulator of cell proliferation is mediated via its interaction with the export receptor CRM1. This protein–protein interaction represents an attractive target in cancer research and therapy. Here, we report a sophisticated strategy addressing Survivin’s nuclear export signal (NES), the binding site of CRM1, with advanced supramolecular tweezers for lysine and arginine. These were covalently connected to small peptides resembling the natural, self-complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 75 publications
3
28
0
Order By: Relevance
“…Nuclear tumor suppressor factors mediated by CRM1 include p53, p21, nuclear phosphosmin (nucleophosmin, NPM), and nuclear factor kappa B inhibitor alpha (IκBα) [ 7 ]. In vitro and in vivo [ 8 ] knock down of CRM1 expression inhibited cell cycle progression and proliferation of OC cells. Survivin is the smallest member of the inhibitor of apoptosis (IAP) gene family and is widely expressed in colorectal cancer, pancreatic cancer, liver cancer, and other tumor tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear tumor suppressor factors mediated by CRM1 include p53, p21, nuclear phosphosmin (nucleophosmin, NPM), and nuclear factor kappa B inhibitor alpha (IκBα) [ 7 ]. In vitro and in vivo [ 8 ] knock down of CRM1 expression inhibited cell cycle progression and proliferation of OC cells. Survivin is the smallest member of the inhibitor of apoptosis (IAP) gene family and is widely expressed in colorectal cancer, pancreatic cancer, liver cancer, and other tumor tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptional selectivity for these two amino acids is achieved by passing the entire amino acid side chain through the cavity and then locking by a phosphonate-ammonium salt bridge [ 118 ]. Conjugates of lysine-selective supramolecular tweezers with covalently linked peptides 95 ELTL 98 and 95 ELTLGEFL 102 based on the motifs corresponding to the BIRC5 interface area were designed [ 119 ]. In the absence of protein partners, BIRC5 monomer-dimer equilibrium is shifted towards the dimer.…”
Section: Targeting Clinically Significant Ppis With Interfacial Peptidesmentioning
confidence: 99%
“…The lysine residue at position 103 located at the very beginning of the C-terminal of BIRC5 has been suggested as the most suitable “anchor” for capture with supramolecular tweezers. Lysine residues 90 and 91 were chosen as alternatives [ 119 ].…”
Section: Targeting Clinically Significant Ppis With Interfacial Peptidesmentioning
confidence: 99%
“…In these examples, the enzyme and signalling molecule are on the same side of the membrane, and without physically decoupling the signal from the effect the membrane serves only to localise components on the vesicle exterior. 69 As far as we are aware, no synthetic transducers have been reported that exploit the compartmentalisation afforded by the lipid bilayer to regulate enzyme activity.…”
Section: Abiotic Mechanisms For Signal Transductionmentioning
confidence: 99%